Implementation of Tahfidz Program in Increasing Community Interest in Madrasah Diniyah - Jauharotul Makniyah; Usnol Khotimah (P3M IAI Nusantara Batang Hari, 2023)
This study aims to describe the implementation of tahfidz program as an effort to increase public interest in madrasah diniyah and the factors that support it. This research uses qualitative methods (observation interview) with the type of case study research at madrasah diniyah Al-Matin in Sentol Pragaan village. This research resulted in several conclusions as follows: The implementation of the Tahfidz Al-Qur'an program can increase community interest in learning with the takrir method, as well as carrying out demonstrations of student memorization witnessed directly by the community and including students in Tahfidz competitions, as well as including the community in annual evaluations. The development of community interest in MDT. Al-Matin with the Tahfidz program has proven to increase, which is indicated by the increasing number of students at MDT. Al-Matin, which was originally only 16 students to 31 students and is also evident from the enthusiasm of the community in following the development of the Al-Qur'an Tahfidz program at MDT. Al-Matin